The Art of Suspicion, or a Heuristic for Understanding of Actions - Norkus, Zenonas (Problemos, 1996)
An attempt is undertaken to expose heuristic rules for an investigator which suspects the sincerity of an acting person and tests her suspicions. There are explored difficulties encountered by an investigator suspecting a person acting under conditions of risk and of uncertainty.